First find a common denominator
1/16(2/2) = 2/32
9/32 - 2/32 = 7/32
7/32 is your answer
hope this helps
Answer:
2x-y-1=0
Step-by-step explanation:
.
Answer:
(c) 0
Step-by-step explanation:
Each of the terms in the expression represents a different transformation of a different trig function. Expressing those as the same trig function can make it easier to find the sum.
__
We can start with the identity ...
cos(x) = sin(x +π/2)
Substituting the argument of the cosine function in the given expression, we have ...
cos(π/2 -θ) = sin((π/2 -θ) +π/2) = sin(π -θ) = -sin(θ -π)
__
The first term, sin(π +θ), is a left-shift of the sine function by 1/2 cycle, so can be written ...
sin(π +θ) = -sin(θ)
The second term is the opposite of a right-shift of the sine function by 1/2 cycle, so can be written ...
cos(π/2 -θ) = -sin(θ -π) = sin(θ)
Then the sum of terms is ...
sin(π +θ) +cos(π/2 -θ) = -sin(θ) +sin(θ) = 0
The sum of the two terms is identically zero.
Answer:
-⅓
Step-by-step explanation:
The formula for slope is y²- y¹/x²- x¹. Plug in the numbers for the equation and you have 4-5/1-(-2).
This gives you -1/3.
64 = 2x2x2x2x2x2
40=2x2x2x5
LCM=8x2x2x2x5=320
LCM= 320